The influence of pricipal leadership, professional attitue, work ethic and school cultureon organizational commitmet and performance of elementary school education in Dukuh Turi Sub District, Tegal District: Human Resaurces - Mujib Digdo Wiguno; Tabrani; Dian Noviany R; Mahben Jalil (Enrichment : Journal of Management, 2023)
The objectives of this study are: Principal leadership, professional attitudes, work ethics and school culture have a positive impact on the performance of personnel and organizational commitment of elementary school educators. Organizational commitment positively affects the performance of educators. The population of this study was all elementary school educators in Dukuhturi Subdistrict, Tegal Regency, totaling 303 people and the sample was taken using the formula from Slovin. In this study, the data collection method used was a questionnaire. The data analysis method of this research is the validity and reliability test of the instrument and quantitative analysis of structural equation modeling (SEM). The results of the study can be concluded that Principal leadership has no a negative impact on commitment of elementary schools. Professional attitudes, and school culture have a positive impact on commitment of elementary schools. Work ethics and school culture have a negative impact on commitment of elementary schools. Principal leadership and professional ethics have a positive impact on the performance of educators elementary schools. Work ethics has a negative impact on the performance of educators elementary schools. Organizational commitment has a positive effect on the performance of educators